2011
DOI: 10.1152/ajpheart.00948.2009
|View full text |Cite
|
Sign up to set email alerts
|

Post-transcriptional silencing of SCN1B and SCN2B genes modulates late sodium current in cardiac myocytes from normal dogs and dogs with chronic heart failure

Abstract: Mishra S, Undrovinas NA, Maltsev VA, Reznikov V, Sabbah HN, Undrovinas A. Post-transcriptional silencing of SCN1B and SCN2B genes modulates late sodium current in cardiac myocytes from normal dogs and dogs with chronic heart failure. Am J Physiol Heart Circ Physiol 301: H1596 -H1605, 2011. First published June 24, 2011 doi:10.1152/ajpheart.00948.2009.-The emerging paradigm for Na ϩ current in heart failure (HF) is that its transient component (INaT) responsible for the action potential (AP) upstroke is decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 49 publications
3
35
0
1
Order By: Relevance
“…The effects of ROS on b-subunits have not been studied as far as we know. However, in one study, experimental heart failure in dogs caused increased I NaL due to slower decay, and this effect was concluded to be due to dysfunctioning of the b1-subunits (186). Regarding this study, it is to note that HF causes increased ROS generation in the FIG.…”
Section: Redox Effects On Sodium Channels and Excitabilitymentioning
confidence: 69%
“…The effects of ROS on b-subunits have not been studied as far as we know. However, in one study, experimental heart failure in dogs caused increased I NaL due to slower decay, and this effect was concluded to be due to dysfunctioning of the b1-subunits (186). Regarding this study, it is to note that HF causes increased ROS generation in the FIG.…”
Section: Redox Effects On Sodium Channels and Excitabilitymentioning
confidence: 69%
“…We also assayed for CaMKII-induced changes in recovery from inactivation but did not observe a significant difference across tested conditions (data not shown). Again, this may reflect the importance of regulatory ␤-subunits in modulating recovery from inactivation and other gating phenomenon (30,(43)(44)(45)(46). Although the use of the heterologous expression system limits the number of functional effects observed, all of the CaMKII-induced functional changes in I Na seen in HEK293 cells are consistent with those observed in myocytes under similar recording conditions (8,15), indicating that this reduced system can be used to dissect components of CaMKII-dependent functional changes in Na V 1.5, and suffice for the CaMKII-induced shifts in availability and intermediate inactivation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Maltsev et al (66) showed that the ␤ 1 -subunit (but not ␤ 2 ) modulates I Na,L produced by heterologously expressed Na V 1.5 by slowing its decay and increasing its amplitude relative to the peak current. Recently, they showed that reduced expression of either ␤ 1 -or ␤ 2 -subunits caused a significant loss of function or gain of function of I Na,L , respectively, in both normal and failing canine myocytes (78). However, there are contrasting results on the modulation of I Na,L by ␤-subunits in heterologous and native systems and whether they modulate similarly cardiac and noncardiac isoforms.…”
Section: Late Na Currentmentioning
confidence: 99%